JUDICIAL REVIEW OF CONSTITUTIONAL COURT DECISION NO. 90/PUU-XXI/2023 CONCERNING AGE LIMITS FOR PRESIDENTIAL AND VICE-PRESIDENTIAL CANDIDATES - M. Faqih Firdaus; Slamet Riyanto (Justitia et Pax, 2025)
The Constitutional Court is an organization of legal power which, in view of the constitution, has a legal capability to maintain regulation and equity. Regulation Number 24 of 2003 makes sense of that the obligations and elements of the Constitutional Court are to deal with established matters in regards to specific protected matters to shield the constitution so it is carried out dependably as per the desire of individuals and majority rule beliefs. In protecting the constitution, obviously, sacred appointed authorities are required who have information and skill in state organization as well as a promise to executing and managing state life as per the passages of the constitution, so every choice gave by the Constitutional Court is a legitimate item that doesn't go external the passageways of the constitution, so the actual constitution is naturally kept up with. This examination is spurred by the significant job of the Constitutional Court in giving over choices since it is as per Article 10 of Regulation No. 24 of 2003 concerning the Constitutional Court, the choice of the Constitutional Court is conclusive and has restricting legitimate power. The overall population, state directors, and all parts of the country trust that the Constitutional Court judges will really complete their capabilities, obligations and commands as per the Constitution, so through Constitutional Appointed authorities who have a statesmanlike soul, the Constitutional Court can create choices that can give a feeling of equity. in the midst of society. Keywords: Equity, Judge's Choice, Constitutional Court.